BIBIT SENGON TAHAN PENYAKIT KARAT PURU: BERAPA RUPIAHKAH PETANI HUTAN RAKYAT BERSEDIA MEMBAYAR? - Evi Irawan (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2014)
Gene modified (GM) based measures to control gall rust disease infestation to Falcataria moluccana are still not applied as one of strategic toolbox of tropical forest disease management. Since the growth and application of biotechnology in the field of forestry is in rapid pace, it is necessary to know to what extent is the acceptance of forestry farmers to GM gall rust resistant Falcataria moluccana seedling. This research is aimed at measuring farmers' willingness to pay toGMgall rust resistant F. moluccana. The data used in this research were derived from field survey of 117 farmers inWonosobo Regency in Central Java and collected using dichotomous choice contingent valuation method. The collected data were then analyzed using non-parametric and parametric approach. The results show that mean of farmers' willingness to pay was IDR 1062/seedling by using non parametric approach and around IDR 1035/seedling to IDR 1075/seedling by using parametric approach. These findings indicate that the majority of farm forestry farmers accept transgenic seedling or, in other words, there is a market for transgenic seedling. Furthermore, the findings can be used as an economic basis in developing transgenic seedling in Indonesia.